2021
DOI: 10.3390/genes12091447
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Role of isomiRs in Cancer: State of the Art and Recent Advances

Abstract: The advent of Next Generation Sequencing technologies brought with it the discovery of several microRNA (miRNA) variants of heterogeneous lengths and/or sequences. Initially ascribed to sequencing errors/artifacts, these isoforms, named isomiRs, are now considered non-canonical variants that originate from physiological processes affecting the canonical miRNA biogenesis. To date, accurate IsomiRs abundance, biological activity, and functions are not completely understood; however, the study of isomiR biology i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 143 publications
(178 reference statements)
0
7
0
Order By: Relevance
“…An earlier attempt to classify 32 cancer types using isomiR profiling was surprisingly successful: even if a "binary" (present or absent) approach was applied, this method could label different tumor types with high (90%) sensitivity and with a very low (3%) false discovery rate (Telonis et al 2017). A recent meta-analysis of available cancer datasets and publications not only supported this approach but could identify specific miRNA isomiRs that can be used as biomarkers for certain tumor types (Zelli et al 2021). A further deep analysis of isomiR datasets could differentiate even among breast cancer subtypes (Nersisyan et al 2022), whereas a recent study provided evidence that the heterogeneous nuclear ribonucleoprotein C (hnRNPC) induced 5' isomiR shift of miR-21-5p could lead to liver cancer (Park et al 2022).…”
Section: Formation Of Isomirs-substantially Increasing the Mirna Repe...mentioning
confidence: 99%
See 1 more Smart Citation
“…An earlier attempt to classify 32 cancer types using isomiR profiling was surprisingly successful: even if a "binary" (present or absent) approach was applied, this method could label different tumor types with high (90%) sensitivity and with a very low (3%) false discovery rate (Telonis et al 2017). A recent meta-analysis of available cancer datasets and publications not only supported this approach but could identify specific miRNA isomiRs that can be used as biomarkers for certain tumor types (Zelli et al 2021). A further deep analysis of isomiR datasets could differentiate even among breast cancer subtypes (Nersisyan et al 2022), whereas a recent study provided evidence that the heterogeneous nuclear ribonucleoprotein C (hnRNPC) induced 5' isomiR shift of miR-21-5p could lead to liver cancer (Park et al 2022).…”
Section: Formation Of Isomirs-substantially Increasing the Mirna Repe...mentioning
confidence: 99%
“…The mechanisms behind isomiR formation have, in general, been revealed: beside the subtle regulation of the main miRNA processing enzymes (Drosha and Dicer), the action of terminal nucleotidyl transferases, exoribonucleases and RNA editing enzymes are also responsible for the existence of certain isomiR groups (Tomasello et al 2021). On the other hand, the regulation of cell-type specific isomiR distribution is still not completely understood and this aspect is currently in the focus of intensive investigations (Zelli et al 2021;Aparicio-Puerta et al 2023). Nevertheless, isomiRs should definitely be considered in miRNA target predictions (Ahmed et al 2014), as well as in the development of new diagnostic tools and in planned therapy applications (Nikolova et al 2021;Scheper et al 2022).…”
Section: Formation Of Isomirs-substantially Increasing the Mirna Repe...mentioning
confidence: 99%
“…In this fashion it does not allow discovery of IsomiR (i.e., miRNA variants of the same miRNA, which can differ in sequence and/or length composition and will bind to different mRNA targets than the original miRNA sequence [ 306 ]) expression ratio differences for a specific miRNA in exosome sub-populations. The study of isomiRs is relevant in cancer, as their expression ratio has been shown to be affected by and can elicit changes in tumor cell migration and invasion [ 307 ]. (2) qPCR assays typically require large inputs of RNAs for global evaluation and may still require a pre-amplification step (i.e., typically ~14 cycles) before the 40-cycle amplification for fluorescent quantification, which leaves room for potential amplification bias or errors.…”
Section: Exosomes: a Source Of Tumor Biomarkersmentioning
confidence: 99%
“…Besides, based on the origin of sequence from opposite arms of pre-miRNA, mature miRNA is annotated with a -5p or -3p, such as miR-20b-5p [ 16 ]. The most important of these findings is that the functions and biological activity of isomiRs are diverse from each other and canonical miRNA [ 17 ].…”
Section: Introductionmentioning
confidence: 99%